Evaluation of lipid profile in patients with cherry angioma: A case–control study in Iraqi patients - Mohammed K. Al-Hattab; Ansaar H. Gahlool; Jinan H. Al-Kalidi (Medical Journal of Babylon)
Abstract Background: Cherry angioma (CA) is a common lesion among adults and elderly people. Both CA and dyslipidemia have vital common areas, such as their effect on elderly people at a certain age and their interaction with the vascular system. Therefore, we have found it to be an interesting topic for our research to investigate the connection between CA and dyslipidemia. Objectives: The motivation of this project is to investigate the association between CA and dyslipidemia among a sample of Iraqi patients. Materials and Methods: A total number of 104 Iraqi people were selected (39 male and 65 female); 52 of them were affected with CA, and the other 52 were healthy controls. For the purpose of assessing lipid profile, we used Beckman Coulter/Olympus—AU480 Chemistry Analyser was used in measuring fasting serum lipid profile parameters, including triglyceride (TG), total cholesterol (Tch), high-density lipoprotein-cholesterol (HDL-C). Results: The results showed a significant difference between patients with CA and control subjects in TG, CHOL, and LDL. The mean levels of the TG, total CHOL, and LDL were significantly higher in cases with CA compared to a group of controls, in which the differences were significant for TG, total CHOL, and LDL (P-value = 0.000). There was no significant difference between the two groups in the mean level of HDL (P-value = 0.059). additionally, there was no significant difference in levels of lipid value regarding ages and sex distribution between patients with CA and controls (P-value > 0.05). Conclusion: Based on its outcomes, the study proposed that dyslipidemia could play a vital role in the pathogenesis of CA lesions. Hence, dyslipidemia treatments may represent an effective means for CA therapy.